2016 Intl IEEE Conferences on Ubiquitous Intelligence &Amp; Computing, Advanced and Trusted Computing, Scalable Computing and C 2016
DOI: 10.1109/uic-atc-scalcom-cbdcom-iop-smartworld.2016.0110
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network and Monte Carlo Simulation in a Hybrid Method for Time Series Forecasting with Generation of L-Scenarios

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…When the error results are compared, it is concluded that the hybrid system has the least amount of errors (Hocaoğlu et al, 2015). Pablo et al (2016) proposed a hybrid approach to the reconstruction of the time series with the creation of ANN and Monte Carlo Simulation. They tried to estimate the daily milk sales of a dairy company using these models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When the error results are compared, it is concluded that the hybrid system has the least amount of errors (Hocaoğlu et al, 2015). Pablo et al (2016) proposed a hybrid approach to the reconstruction of the time series with the creation of ANN and Monte Carlo Simulation. They tried to estimate the daily milk sales of a dairy company using these models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They tried to estimate the daily milk sales of a dairy company using these models. The results show that the proposed method can reconstruct the past and predict the future from the known time series segment (Pablo, et al, 2016). Sugiartawan, Pulungan, and Sari (2017) used a hybrid model that they created with wavelet transform and LSTM in order to predict the number of tourists coming to Indonesia over a monthly period.…”
Section: Literature Reviewmentioning
confidence: 99%